Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Dengan Lingkungan Kerja Sebagai Variabel Moderasi - Hendri Rasminto; Febryantahanuji Febryantahanuji; Danang Danang (STEKOM PRESS, 2020)
This study aims to analyze the effect of work discipline on employee performance with the Work Environment as a Moderation Variable. At one of the private universities in Semarang. The sample is all members of the population using a saturated sampling method. The analytical tool used in this research is Moderation Regression Analysis. Hypothesis 1 testing shows that the value of t count = 2.745> t table = 1.645 with a significance number = 0.005 < = 0.05 (significant). So (H1) which states that work discipline has a positive effect on employee performance is proven. Regression coefficient β1 = 0.257 (positive sign), this can be interpreted that the higher the work discipline, the higher the employee performance. Hypothesis testing 2. Testing (H2) shows that the t value of the influence of the moderating variable is 2.599> t table = 1.645 with a significance number = 0.016 < = 0.05 (significant). (H2) which states that the Work Environment positively moderates the effect of Work Discipline on Employee Performance. The interaction test shows β2 = 0.175 (positive sign), this can be interpreted that a good work environment will strengthen the effect of work discipline on employee work discipline. Keywords: work discipline, Employee performance, Work environment